Enhanced narrow green emission and thermal stability in γ-AlON: Mn2+, Mg2+ phosphor via charge compensation. Issue 9 (15th June 2019) - Dong, Quan; Yang, Fengli; Cui, Jun; Tian, Yabin; Liu, Shuifu; Du, Fu; Peng, Jiaqing; Ye, Xinyu
Abstract: A series of novel green emitting γ -AlON: Mn 2+, Mg 2+ and γ -AlON: Mn 2+, Mg 2+, M (M = Li +, Na +, K +, Si 4+ ) phosphors were fabricated with the gas-pressure sintering reaction process. The phase structure, morphology and photoluminescence properties of the phosphors were characterized via X-ray powder diffraction, scanning electron microscopy, and photoluminescence spectroscopy. Meanwhile, the charge compensation methods were utilized to eliminate the disadvantage of charge imbalance between Al 3+ and Mn 2+ . The results show that the luminescence intensity of Mn 2+ was maximally enhanced by the introduction of Si 4+ ions, which was 2.36 times that of the sample without charge compensator. Moreover, as the temperature reached at 150 °C, thermal stability of the samples contained charge compensator Li + and Si 4+ were improved to 93% and 90% of that the room temperature, respectively, while the original sample was 85%. These luminescence properties were enhanced due to the introduction of charge compensators which reduce defects caused by charge imbalance. In addition, the specific mechanisms were discussed in detail. In general, the charge compensation could be used as an effective strategy to strengthen thermal stability and luminescence performances of phosphors.